2007
DOI: 10.1159/000104152
|View full text |Cite
|
Sign up to set email alerts
|

H<sub>2</sub>O<sub>2</sub> Accelerates Cellular Senescence by Accumulation of Acetylated p53 via Decrease in the Function of SIRT1 by NAD<sup>+</sup> Depletion

Abstract: It has been reported that p53 acetylation, which promotes cellular senescence, can be regulated by the NAD+-dependent deacetylase SIRT1, the human homolog of yeast Sir2, a protein that modulates lifespan. To clarify the role of SIRT1 in cellular senescence induced by oxidative stress, we treated normal human diploid fibroblast TIG-3 cells with H2O2 and examined DNA cleavage, depletion of intracellular NAD+, expression of p21, SIRT1, and acetylated p53, cell cycle arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(128 citation statements)
references
References 45 publications
9
118
0
1
Order By: Relevance
“…4B). These findings are compatible to the previous finding of H 2 We then examined whether ROS, as induced by toxic compounds or direct exposure of H 2 O 2 , was the cause of the increased p21 expression and cell cycle arrest in L-PDMCs, since this has been reported previously (16,22). However, we found that NAC inhibition of H 2 O 2 accumulation had no effect on cell cycle arrest (Fig.…”
supporting
confidence: 91%
“…4B). These findings are compatible to the previous finding of H 2 We then examined whether ROS, as induced by toxic compounds or direct exposure of H 2 O 2 , was the cause of the increased p21 expression and cell cycle arrest in L-PDMCs, since this has been reported previously (16,22). However, we found that NAC inhibition of H 2 O 2 accumulation had no effect on cell cycle arrest (Fig.…”
supporting
confidence: 91%
“…As additional evidence for a role of ROS in aging, increased expression of the antioxidant enzyme catalase in mitochondria of transgenic mice can extend life-span and reduce age-related changes in tissues such as that of the heart [10][11][12]. It is well known that damaged mitochondria release harmful ROS into the cytosol [25][26][27][28][29][30]. In the present study, we demonstrated an excessive generation of oxidative stress, such as ROS, through mitochondrial damage in young rat AF cells treated with high glucose concentrations with a dose-and time-dependent manner compared to normal control.…”
Section: Discussionmentioning
confidence: 99%
“…ROS are thought to play a role in various cellular processes, such as senescence, which appear to cause cellular damage and lack of physiological function. Therefore, the accumulation of ROS has been reported to be associated with a variety of diseases including neurodegenerative diseases, DM, cancer, premature aging, and inflammatory disorders [29,30]. To date, little information is available about the effect of DM on the senescence of young AF cells and premature intervertebral disc degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Sirtuin 1 (Sirt1), the closest homologue of silent information regulator2 (Sir2), has been identified to be a NAD + -dependent deacetylase whose activity plays a significant role in the processes of senescence, apoptosis and cell cycle modulation by regulating the acetylation of lysine groups of many transcriptional factors and proteins, such as histones, p53 and FOXO transcriptional factors [17][18][19] . In addition, oxidative stress has been shown to reduce the cellular NAD + content by suppressing the activation of intracellular nicotinamide phosphoribosyltransferase (iNampt), the rate-limiting enzyme for NAD + biosynthesis derived from nicotinamide (NAM), and decreasing the Sirt1 activity 10,[20][21][22] . Therefore, Sirt1 is considered to be a key player in the promotion of oxidative stress-mediated cellular senescence 23) .…”
Section: Cell Culturementioning
confidence: 99%